Women lighthouse keepers of Lake Michigan : heroic tales of courage and resourcefulness - Mason, Kathy S., 1970- (The Edwin Mellen Press, 2012)
This book focuses on the fascinating careers of the women who tended lighthouses on Lake Michigan in the late nineteenth and early twentieth centuries. It explores with great acuity how a number of special women gained their lighthouse positions and dealt with unique challenges of their time and place.